Clinical comparison of metal ceramic resin-bonded fixed dental prostheses with a conventional and a mixed retainer design - Bömicke, Wolfgang; Kappel, Stefanie; Stober, Thomas; Rammelsberg, Peter (The journal of prosthetic dentistry, 2014)
STATEMENT OF PROBLEM: Little is known about the clinical performance of fixed dental prostheses that rigidly connect adhesive retainers and crowns. - PURPOSE: The purpose of this retrospective analysis was to assess and compare the clinical performance of resin-bonded fixed dental prostheses with a conventional and a mixed retainer design. - MATERIAL AND METHODS: Included as participants were all patients of the hospital since 2004 with regular clinical follow-up who were treated with 3-unit or 4-unit metal ceramic resin-bonded fixed dental prostheses with a conventional 2-adhesive retainer design (conventional group) or with a mixed type combining an adhesive retainer with a crown or a partial crown retainer (mixed group). The analysis included 84 participants with a total of 57 (64%) prostheses in the conventional group and 32 (36%) prostheses in the mixed group. Treatment and data collection were standardized. Cumulative survival without failure (defined as a restoration in need of replacement), chipping, and debonding were estimated by the Kaplan-Meier method and compared for the groups (log-rank test) (α=.05). - RESULTS: During a mean observation period of 4.1 years (SD, 2.5 years; minimum, 0.4 years; maximum, 9.4 years), 12 complications occurred in 10 restorations. Defects of the ceramic veneer (n=6) were observed most frequently. The estimated 5-year failure-free survival rate was 97.4% (standard error, .025) in the conventional group and 95% (standard error, .049) in the mixed group (log-rank, P=.32). The 5-year cumulative survival rate without chipping was 90.7% (standard error, .064) for the conventional group and 93.8% (standard error, .061) for the mixed group (log-rank, P=.44). The 5-year cumulative survival rate without debonding was 95.1% (standard error, .034) for the conventional group and 91.5% (standard error, .058) for the mixed group (log-rank, P=.54). - CONCLUSIONS: Limited by a small sample size and a short follow-up period, the findings of this retrospective analysis indicate that the clinical performance, in terms of survival and the incidence of complications, is comparable for conventional resin-bonded fixed dental prostheses and those that rigidly connect an adhesive wing and a partial or complete crown. Acceptable 5-year survival and complication rates imply that the medium-term prognosis for resin-bonded restorations with a retentive preparation design is comparable with that for conventional fixed dental prostheses.
Gesehen am 10.09.2020